2017
DOI: 10.1051/meca/2017018
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional study of parallel shear flow around an obstacle in water channel and air tunnel

Abstract: The purpose of this study is to show the effect of some physical parameters on a parallel shear flow. The variation of the velocity inlet and the influence of an obstacle placed at the bottom of a channel were analyzed. The governing equations based on K-e model in a line source downstream around a three-dimensional obstacle are determined by the finite volume method with SIMPLEC algorithm. The obtained results have allowed to establish the dynamic characteristics of this kind of flow. Horizontal and vertical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The K-e standard turbulence model leads to the best agreement between the numerical results of reference [20] and the experimental results of reference [18] for the water channel. This model will be adapted in all the rest of work.…”
Section: Mathematical Modelmentioning
confidence: 74%
See 3 more Smart Citations
“…The K-e standard turbulence model leads to the best agreement between the numerical results of reference [20] and the experimental results of reference [18] for the water channel. This model will be adapted in all the rest of work.…”
Section: Mathematical Modelmentioning
confidence: 74%
“…The physical presentation of the proposed problem is shown in Figure 1. We have used the same geometry of [20]. The temperature above the obstacle is constant (T 1 = 15°C), while that around the obstacle is variable (T 2 = 15, 20, 25, and 35°C).…”
Section: Physical Presentation Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of other studies have provided evidence that, as the space between obstacles is decreased, the fluid flow in the channel is consequently enhanced, and that an increase in the Reynolds number (Re) enhances the process of heat removal around the obstacles, chiefly around the obstacle corners [2][3][4]. In a numerical study, Mohamed Toumi et al [5] investigated the three-dimensional shearing flows of Newtonian fluids around a cuboid obstacle. Their results showed that the locations after the obstacle and collision by the turbulent shearing flow generally formed a recirculation area with a high concentration scalar; this means the area at the boundary layer after the obstacle contained great turbulent energy.…”
Section: Introductionmentioning
confidence: 99%